Anion exchange membrane containing a spiro ring structure, a preparation method thereof, and an electrochemical device
Patent Information
- Application Number
- CN202611246622.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]为了解决现有阴离子交换膜存在离子传导能力与尺寸稳定性难以兼顾的固有限制,同时强碱工况下易发生聚合物骨架降解、季铵基团发生霍夫曼消除造成膜性能快速衰减的技术问题,本发明旨在提供一种含螺环结构的阴离子交换膜及其制备方法和电化学器件
[0019] In a preferred embodiment, the quaternized copolymer polymer can be formed into a self-standing film for use as a solid membrane in an anion exchange membrane water electrolyzer, and/or dispersed in the catalyst layer as an ionomer binder for the electrode catalyst layer. The homologous quaternized copolymer polymer of this invention has dual application forms: it can be formed into a self-standing film as a solid membrane to block materials at both electrodes and conduct anions; it can also be dissolved and dispersed in the catalyst layer as an ionomer binder phase to construct a continuous three-phase ion transport channel. The membrane and ionomer materials have a homologous skeleton and their ion transport characteristics are mutually matched, effectively reducing the membrane electrode interface impedance and improving the overall working efficiency of the electrolysis device.
Smart Images

Figure CN122917263A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer functional membrane materials and electrochemical technology, and more specifically relates to an anion exchange membrane with a spirocyclic structure, its preparation method, and electrochemical device. Background Technology
[0002] The global energy system is accelerating its transformation towards a clean and low-carbon future. Hydrogen energy, with its high energy density and zero-carbon emissions from combustion, has become a key green energy carrier for achieving deep industrial decarbonization. Anion exchange membrane electrolysis (AEMWE) technology combines the advantages of traditional alkaline water electrolysis and proton exchange membrane electrolysis, representing a cutting-edge core route for low-cost, large-scale green hydrogen production. This technology uses polymer anion exchange membranes (AEM) as the solid electrolyte and anode / cathode separator, enabling stable operation in pure water or weakly alkaline environments. The catalytic electrode can utilize abundant and inexpensive nickel, iron, and cobalt-based non-precious metals. The electrolyzer can employ a compact, zero-gap structure, offering advantages such as high current density and rapid start-up and shutdown response, demonstrating significant commercial potential.
[0003] Under actual electrolyzer operating conditions, AEM membranes are prone to irreversible performance degradation, exhibiting two major defects: First, traditional AEMs use a polymer backbone containing aromatic ether bonds. Strong nucleophilic hydroxyl ions continuously attack the ether bond sites within the system, causing ether bond breakage and backbone degradation, directly reducing the mechanical strength of the membrane and inducing microcracks, gas leakage, or even overall membrane failure. Second, there is an inherent trade-off between the membrane's hydroxyl conductivity and dimensional stability: increasing membrane conductivity is generally achieved by increasing the number of functional groups, i.e., increasing the ion exchange equivalent (IEC). However, increasing the IEC often leads to excessive water absorption and swelling in the AEM, resulting in decreased dimensional stability. Conversely, decreasing the IEC usually leads to decreased conductivity, affecting the efficiency of hydrogen production through electrolysis.
[0004] To improve the overall performance of AEM (Anion Electrode Membrane), current research often introduces sterically hindered, twisted rigid aromatic rings into the polymer backbone to break the tight packing of molecular chains and construct a high free volume, thereby improving hydroxide ion conduction efficiency while maintaining a certain IEC (Internal Equivalence). Other studies have mitigated high-temperature swelling of the film by controlling the rigidity of the backbone and introducing local crosslinking. However, these conventional rigid modification methods can only optimize performance in one direction and cannot achieve a synergistic balance of multiple indicators, still exhibiting two major shortcomings: First, simply introducing rigid aromatic rings only loosens the molecular packing and increases the free volume, which, while improving conductivity, significantly increases the film's water absorption rate, exacerbating swelling and making it difficult to balance high ionic conductivity and dimensional stability. Second, relying solely on planar rigid structures or crosslinking systems cannot restrict molecular chain creep under strong alkali and high-potential environments, leading to localized cracking of the film during long-term operation and insufficient long-term mechanical stability of the device. Therefore, how to simultaneously construct continuous high-speed anion transport channels, ensure high ion conduction efficiency, and constrain molecular chain creep to achieve low swelling and long-term resistance to strong alkalis is a key technical challenge that urgently needs to be overcome in this field. Summary of the Invention
[0005] To address the inherent limitations of existing anion exchange membranes in balancing ion conductivity and dimensional stability, as well as the rapid performance degradation caused by polymer backbone degradation and Hoffmann elimination of quaternary ammonium groups under strongly alkaline conditions, this invention aims to provide an anion exchange membrane with a spirocyclic structure, its preparation method, and an electrochemical device thereof.
[0006] According to the present invention, the anion exchange membrane containing a spirocyclic structure has a quaternized copolymer polymer backbone that does not contain aromatic ether bonds, and its structural formula is as follows:
[0007]
[0008] In the formula: Ar is an aryl monomer, R is any one or more of C1-C10 alkyl or haloalkyl groups, and x = 0.05-0.2. This invention increases the free volume of the polymer by introducing spirocyclic structural units into the polymer backbone and constructing a stable polymer skeleton by combining them with aromatic rigid structural units. Furthermore, by controlling the structure of the substituent R, a tunable microphase separation structure is formed within the polymer, optimizing the hydroxide ion transport channel and improving ionic conductivity while maintaining dimensional stability and mechanical properties. By controlling the copolymerization ratio of spirocyclic and aromatic structural units and the structure of the substituent R, the ion exchange capacity, free volume, and microphase separation structure of the polymer can be further optimized to meet the application requirements of different electrochemical devices. Simultaneously, the polymer backbone does not contain aromatic ether bonds, which avoids ether bond breakage and degradation caused by hydroxyl nucleophilic attack under strongly alkaline conditions, thus improving the alkali resistance stability of the anion exchange membrane at the molecular skeleton level.
[0009] In a preferred embodiment, the aryl monomer comprises any one or more of the following structures:
[0010] , , , , , , , , , , , , , , , , This invention allows for the selection of different rigid aromatic ring units for copolymerization, flexibly controlling the compactness of polymer chain stacking, hydrophobicity, and mechanical entanglement; it can also target the ion conductivity, water swelling rate, and mechanical properties of thin films according to the application scenario, thus broadening the adjustable range of material formulations.
[0011] In a preferred embodiment, orthogonally twisted 6,6'-dialkoxy-3,3,3',3'-tetramethyl-1,1'-spirobiindenene rigid units and aryl copolymer units are simultaneously embedded in the all-carbon backbone of the polymer, with piperidine quaternary ammonium groups directly bonded to the polymer backbone. This invention breaks the regular, tightly packed aromatic polymer chains through the orthogonally twisted spirobiindenene units, constructing continuous and stable hydroxide transport channels within the membrane and improving ionic conductivity. Simultaneously, the stereoheliocyclic rigid structure restricts polymer chain movement, reducing excessive water absorption and swelling of the membrane; the piperidine quaternary ammonium directly connects to the backbone, ensuring stable spatial arrangement and further enhancing the chemical stability of the groups under strongly alkaline conditions.
[0012] In a preferred embodiment, the aryl copolymer unit is selected from either m-terphenyl or 9,9-dimethylfluorene. When the aryl copolymer unit is m-terphenyl: the m-terphenyl unit can improve the rigidity of the polymer backbone, resulting in high tensile strength and excellent tear resistance after polymer film formation, making it suitable for preparing solid anion exchange membranes for water electrolyzers; when the aryl copolymer unit is 9,9-dimethylfluorene: the polymer's hydrophobicity is improved, resulting in better compatibility with electrocatalytic powders, making it suitable for use as a catalyst layer ionomer to construct a continuous three-phase ion transport interface; the molecular skeletons of the two types of polymers are homologous, and when used together, the ion transport channels are matched, which can reduce the interfacial impedance of the membrane electrode.
[0013] The preparation method of the anion exchange membrane containing a spirocyclic structure according to the present invention includes the following steps: S1, dissolving aryl-structured reactants and ketone reactants in a first organic solvent, reacting under superacid catalysis to obtain a polymer solution with a piperidine structure, then adding a first precipitant for precipitation, washing and drying to obtain a polymer powder with a piperidine structure; S2, dissolving the polymer powder with a piperidine structure in a second organic solvent, reacting with a methylating agent and a basic agent, then adding a second precipitant for precipitation, washing and drying to obtain a quaternized polymer powder; S3, dissolving the quaternized polymer powder in a third organic solvent, then drying the solvent to obtain an ion exchange membrane. The present invention employs superacid-catalyzed polymerization to first construct an aryl polymer backbone containing piperidine tertiary amine side groups, then achieving quaternization modification through a methylation reaction, and finally processing the solution into a membrane. The polymerization reaction conditions are mild and the reaction path is simple; the polymer is purified by precipitation, washing and drying, effectively removing small molecule impurities; the quaternization step introduces an alkaline reagent to neutralize residual acidic substances in the polymerization system and promote the forward methylation reaction; the polymer is soluble in organic solvents, is suitable for solution processing and molding processes, and can stably prepare the target anion exchange membrane, with strong process versatility.
[0014] In a preferred embodiment, the ketone reactants comprise one or more of the following carbonyl compound structures:
[0015] , , , , , , , This invention uses a variety of carbonyl compounds as reaction raw materials, which can flexibly control the substitution structure of piperidine groups on the polymer chain, adjust the spatial environment of quaternary ammonium cations, and thus regulate the alkali resistance and ion conductivity of the anion exchange membrane, broadening the range of raw material selection and the adjustable range of material properties.
[0016] In a preferred embodiment, the molar ratio of aryl reactant to ketone reactant in step S1 is 1:(1.1~1.2), and the molar ratio of aryl reactant, first organic solvent, and superacid is 1:(50~120):(10~40). By controlling this feed ratio, the present invention ensures that the aryl reactant fully participates in the polymerization reaction, increasing the polymer molecular weight and reducing small molecule byproducts; the sufficient amount of superacid ensures the polymerization reaction activity while avoiding excessive superacid from causing a burden on post-processing; and the solvent amount ensures that the reactants are fully dissolved, achieving homogeneous polymerization, improving polymer structural uniformity, and reducing cross-linking and chain-severing defects.
[0017] In a preferred embodiment, the molar ratio of the second organic solvent, the methylating agent, and the basic reagent in step S2 is (100~200):(2~10):(1~5). Within this ratio range, sufficient methylating agent ensures that the piperidine tertiary amine is fully converted into quaternary ammonium groups, thereby increasing the ion exchange capacity; the amount of basic reagent matches the acid neutralization requirements of the system, promoting the quaternization reaction; and sufficient organic solvent ensures that the polymer is fully dissolved, realizing the transformation of heterogeneous to homogeneous reaction, improving the uniformity of the quaternization reaction, and avoiding incomplete local reactions.
[0018] The electrochemical device according to the present invention comprises an anion exchange membrane obtained by molding the above-mentioned quaternized copolymer polymer. The anion exchange membrane prepared by the quaternized copolymer polymer of the present invention has a rigid structure with an ether-free all-carbon backbone and a twisted spirocyclic ring, which combines excellent hydroxide ion conductivity, low water swelling rate, and long-term alkali resistance stability under high temperature and strong alkaline conditions, thereby improving the operating current density and continuous service life of the electrochemical device.
[0019] In a preferred embodiment, the quaternized copolymer polymer can be formed into a self-standing film for use as a solid membrane in an anion exchange membrane water electrolyzer, and / or dispersed in the catalyst layer as an ionomer binder for the electrode catalyst layer. The homologous quaternized copolymer polymer of this invention has dual application forms: it can be formed into a self-standing film as a solid membrane to block materials at both electrodes and conduct anions; it can also be dissolved and dispersed in the catalyst layer as an ionomer binder phase to construct a continuous three-phase ion transport channel. The membrane and ionomer materials have a homologous skeleton and their ion transport characteristics are mutually matched, effectively reducing the membrane electrode interface impedance and improving the overall working efficiency of the electrolysis device.
[0020] This invention constructs a high free volume by introducing spirocyclic structural units into the all-carbon polymer backbone, and uses substituents R to regulate the polymer's micro-phase separation structure. These substituents, along with aromatic rigid units, jointly construct the polymer framework. The spirocyclic three-dimensional twisted configuration opens up the gaps between molecular chains to form continuous hydroxide ion transport channels. Simultaneously, the high rigidity of the spirocyclic structure constrains the water absorption and creep of the molecular chains, breaking the inherent contradiction between ion conductivity and dimensional stability in existing membranes. This ensures rapid hydroxide ion transport while improving the membrane's dimensional stability and mechanical properties. The polymer backbone contains no aromatic ether bonds, eliminating ether degradation sites that hydroxide ions can attack, significantly improving the membrane's long-term chemical stability under strong alkaline conditions. Furthermore, piperidine quaternary ammonium cations are directly embedded and bonded into the polymer backbone, inhibiting degradation pathways such as Hoffmann elimination and nucleophilic substitution. By leveraging the adjustability of copolymerization ratio, aryl units, and substituents, it can be adapted to the operating conditions of different electrochemical devices. The quaternized polymer obtained by the superacid one-step copolymerization process based on this molecular framework can be processed into water electrolysis membranes and catalyst layer ionomers, respectively. When applied to anion exchange membrane water electrolysis devices, it can reduce interfacial impedance and increase hydrogen production current density, taking into account both the convenience of material preparation and the adaptability to industrial hydrogen production conditions. It effectively solves the core defects of existing anion exchange membranes, such as easy aging in strong alkaline environments, difficulty in balancing ion conductivity and dimensional stability, and high cost of preparing membrane-ionomer dual materials. Attached Figure Description
[0021] Figure 1 The above are the 1H NMR spectra of the polymer intermediates in Examples 1-3 of this invention.
[0022] Figure 2 The hydrogen nuclear magnetic resonance spectra of the functional polymers in Examples 1-3 of this invention are shown.
[0023] Figure 3 The above are the 1H NMR spectra of the polymer intermediates in Examples 4-6 of this invention.
[0024] Figure 4 The hydrogen nuclear magnetic resonance spectra of the functional polymers in Examples 4-6 of this invention are shown.
[0025] Figure 5 The NMR spectrum of the polymer intermediate in Comparative Example 1 is shown in 1H NMR.
[0026] Figure 6 The hydrogen NMR spectrum of the functional polymer in Comparative Example 1 is shown.
[0027] Figure 7 The graphs show the tensile stress-elongation at break of the anion exchange membranes in Examples 1-3 of the present invention and Comparative Example 1.
[0028] Figure 8 The graphs show the changes in water content of the anion exchange membranes in Examples 1-3 and Comparative Example 1 at different temperatures.
[0029] Figure 9 The graphs show the changes in the upper swelling rate of the anion exchange membranes in Examples 1-3 and Comparative Example 1 at different temperatures.
[0030] Figure 10 The graphs show the changes in hydroxide ion conductivity at different temperatures for the anion exchange membranes of Examples 1-3 and Comparative Example 1 of this invention.
[0031] Figure 11 The graph shows the voltage-current density polarization performance comparison of the anion exchange membrane assembled electrolyzers of Examples 1-3 and Comparative Example 1.
[0032] Figure 12 The graph shows a comparison of the polarization performance of the electrolyzers prepared by combining the diaphragm of Example 2 with the ionomers of Examples 4-6. Detailed Implementation
[0033] The present invention will now be described in detail with reference to the accompanying drawings and embodiments. The following embodiments are only used to explain the present invention and are not intended to limit the scope of protection of the present invention. Equivalent substitutions and improvements made by those skilled in the art based on the concept of the present invention shall all fall within the scope of protection of the present invention. Unless otherwise specified, all raw materials of the present invention are commercially available raw materials.
[0034] This invention first provides an anion exchange membrane with a spirocyclic structure, wherein the quaternized copolymer polymer constituting the anion exchange membrane has a full carbon backbone without aromatic ether bonds, and its structural formula is as follows:
[0035]
[0036] In the formula: Ar is an aryl monomer, R is any one or more of C1~C10 alkyl or haloalkyl, and x = 0.05~0.2.
[0037] In a preferred embodiment, the aryl monomer comprises any one or more of the following structures:
[0038] , , , , , , , , , , , , , , , , .
[0039] In a preferred embodiment, the polymer backbone simultaneously incorporates orthogonally twisted 6,6'-dialkoxy-3,3,3',3'-tetramethyl-1,1'-spirobisindene rigid units and aryl copolymer units, with piperidine quaternary ammonium groups directly bonded to the polymer backbone.
[0040] In a preferred embodiment, the aryl copolymer unit is selected from one of m-terphenyl and 9,9-dimethylfluorene.
[0041] In a preferred embodiment, the molar ratio of the spiro-ring unit copolymer is limited to the range of x = 0.05~0.2, which can precisely control the total free volume inside the membrane and the rigid support strength of the molecular skeleton. Within the range, the water storage capacity and dimensional stability of the membrane can be balanced as needed, avoiding the defects of insufficient free volume due to too low a spiro-ring ratio and decreased membrane mechanical strength due to too high a ratio. Except for the three preferred ratios of m = 0.05, 0.1, and 0.2, any value within the range of 0.05~0.2 can achieve the core technical effect of the present invention, with only slight differences in performance.
[0042] In a preferred embodiment, x=0.1. By setting the molar ratio of spirocyclic copolymer to 0.1, this invention enables the four core properties of the membrane—mechanical tensile strength, hydroxide ion conductivity, high-temperature swelling resistance, and electrolytic hydrogen production output current density—to simultaneously achieve an optimal balance, resulting in overall performance superior to other samples within the same range.
[0043] The present invention also provides a method for preparing the above-mentioned anion exchange membrane containing a spirocyclic structure, which first includes step S1, dissolving aryl structure reactants and ketone reactants in a first organic solvent, reacting them under superacid catalysis to obtain a polymer solution with a piperidine structure, and then adding a first precipitant to precipitate, wash and dry to obtain a polymer powder with a piperidine structure.
[0044] In a preferred embodiment, the aryl-structured reactant comprises any one or more of the following structures:
[0045] , , , , , , , , , , , , , , , , .
[0046] In a preferred embodiment, the ketone reactants comprise one or more of the following carbonyl compound structures:
[0047] , , , , , , , .
[0048] In a preferred embodiment, the molar ratio of the aryl structure reactant to the ketone reactant is 1:(1.1~1.2), and the molar ratio of the aryl structure reactant, the first organic solvent, and the superacid is 1:(50~120):(10~40).
[0049] In a preferred embodiment, the first organic solvent is selected from one or more of dichloromethane, toluene, and chloroform.
[0050] In a preferred embodiment, the superacid is selected from one or more of trifluoromethanesulfonic acid, trifluoroacetic acid, and perfluorosulfonic acid.
[0051] In a preferred embodiment, the first precipitant is selected from one or more of methanol, ethanol, isopropanol, deionized water, diethyl ether, petroleum ether, ethyl acetate, chloroform, and n-hexane.
[0052] In a preferred embodiment, the polymerization reaction is carried out in an ice bath at 0-5°C with the superacid added slowly, and the reaction time is adjusted to 2-8 hours according to the monomer ratio. After precipitation, the mixture is washed alternately with potassium carbonate aqueous solution and deionized water until no alkaline residue remains.
[0053] The preparation method of the present invention further includes step S2, in which the polymer powder having a piperidine structure is dissolved in a second organic solvent, reacted with a methylating agent and a basic agent, and then added to a second precipitant for precipitation, washing and drying to obtain a quaternized polymer powder.
[0054] In a preferred embodiment, based on the amount of piperidine repeating units in the polymer having a piperidine structure, the molar ratio of the second organic solvent, the methylating agent, and the basic agent is 1:(100~200):(2~10):(1~5).
[0055] In a preferred embodiment, the second organic solvent is selected from one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0056] In a preferred embodiment, the methylating agent is selected from one or more of iodomethane, dimethyl sulfate, dimethyl carbonate, and methyl trifluoromethanesulfonate.
[0057] In a preferred embodiment, the alkaline reagent is selected from one or more of potassium carbonate, cesium carbonate, sodium carbonate, triethylamine, pyridine, and sodium hydride.
[0058] In a preferred embodiment, the second precipitant is selected from one or more of methanol, ethanol, isopropanol, deionized water, diethyl ether, petroleum ether, ethyl acetate, chloroform, and n-hexane.
[0059] The preparation method of the present invention finally includes step S3, which involves dissolving the quaternized polymer powder in a third organic solvent and then drying the solvent to obtain an ion exchange membrane.
[0060] In a preferred embodiment, the third organic solvent is selected from one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0061] In a preferred embodiment, the quaternization powder has a mass-volume concentration of 5-20% (w / w) during membrane preparation.
[0062] In a preferred embodiment, the drying temperature is 50~140°C.
[0063] The electrochemical device according to the present invention comprises an anion exchange membrane obtained by molding the above-mentioned quaternized copolymer polymer.
[0064] In a preferred embodiment, the quaternized copolymer polymer can be formed into a self-standing film for use as a solid membrane in an anion exchange membrane water electrolyzer, and / or dispersed in the catalyst layer as an electrode catalyst layer ionomer binder.
[0065] In a preferred embodiment, under test conditions of 60°C, 1 mol / L KOH, and an applied voltage of 2.0 V: when a film made of the quaternized copolymer polymer is used as the separator, the electrolysis current density is ≥4.6 A / cm². 2 When the aforementioned quaternized copolymer is used as the ionomer of the catalyst layer, the electrolysis current density is ≥6.5 A / cm². 2 .
[0066] The complete synthetic route of the spirobiinden and meta-terphenyl copolymer quaternized polymer of the present invention is as follows, where m is the molar percentage of the spirobiinden unit copolymer, and the value ranges from 0.05 to 0.2.
[0067]
[0068] Example 1: m=0.05
[0069] (1) Synthesis of 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobine: Bisphenol A was stirred and heated to 140°C under a nitrogen atmosphere until it was completely dissolved, and then methanesulfonic acid was added dropwise. The reaction was allowed to proceed for 6 hours. After the reaction was completed, the viscous liquid was poured into distilled water to precipitate the solid, and then washed and filtered with deionized water. Finally, the solid was recrystallized from anhydrous ethanol / distilled water (10:1) to obtain pure white solid 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobine.
[0070] (2) Synthesis of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine: The 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobine obtained in step S1 was dissolved in DMF, potassium carbonate was added and stirred for 15-20 min, then iodomethane was slowly added dropwise, and the reaction was carried out at room temperature for 24 h; the product after the reaction was completed was poured into ice water to precipitate, then filtered and washed several times to finally obtain pure white solid 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine;
[0071] (3) Synthesis of polymer intermediates: 1 g of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine and 13 g of m-terphenyl obtained in step (2) of this example were dissolved in 48 mL of dichloromethane. After complete dissolution, 8.1 g of N-methyl-4-piperidinone was added. Then, 48 mL of trifluoromethanesulfonic acid and 6 mL of trifluoroacetic acid were slowly added dropwise under ice bath to carry out Friedel-Crafts hydroxyalkylation reaction. After 8 h of reaction, a red viscous high molecular weight polymer was obtained. Then, a mixed solution of methanol and deionized water in a volume ratio of 1:1 was added to obtain a pure white fibrous polymer. After being cut into pieces, it was repeatedly washed with 1 M potassium carbonate aqueous solution and deionized water until the supernatant did not turn red after adding phenolphthalein indicator. Then, the purified product was placed in an 80 °C vacuum drying oven and dried for 24 h to obtain a light yellow polymer intermediate powder.
[0072] (4) Synthesis of functionalized polymer: Take 2g of the polymer intermediate powder obtained in step (3) of this embodiment and dissolve it in 50mL of dimethyl sulfoxide. Then add 2g of potassium carbonate and 1mL of iodomethane in sequence. React at room temperature in the dark for 24h. After the reaction is completed, slowly pour the polymer solution into 500mL of ethyl acetate to precipitate. After filtration, wash repeatedly with deionized water. Then place the purified product in an 80℃ vacuum drying oven and dry for 24h to obtain a light yellow functionalized polymer powder.
[0073] (5) Preparation of anion exchange membrane: Take 1g of the functionalized polymer powder obtained in step (4) of this embodiment and dissolve it in 8.2mL of dimethyl sulfoxide to obtain a film-forming solution with a target polymer mass concentration of 10%. Then, dry it at 100℃ by casting or casting method to obtain anion exchange membrane.
[0074] Example 2: m=0.1
[0075] (1) The synthesis of 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobine was the same as in Example 1, step (1);
[0076] (2) The synthesis of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine was the same as step (2) in Example 1;
[0077] (3) Synthesis of polymer intermediates: 1 g of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine and 6 g of m-terphenyl obtained in step (2) of this example were dissolved in 30 mL of dichloromethane. After complete dissolution, 4.6 g of N-methyl-4-piperidinone was added. Then, 24 mL of trifluoromethanesulfonic acid and 3.6 mL of trifluoroacetic acid were slowly added dropwise under ice bath to carry out Friedel-Crafts hydroxyalkylation reaction. After 8 h of reaction, a red viscous high molecular weight polymer was obtained. Then, a mixed solution of methanol and deionized water in a volume ratio of 1:1 was added to obtain a pure white fibrous polymer. After being cut into pieces, it was repeatedly washed with 1 M potassium carbonate aqueous solution and deionized water until the supernatant did not turn red after adding phenolphthalein indicator. Then, the purified product was placed in an 80 °C vacuum drying oven and dried for 24 h to obtain a light yellow polymer intermediate powder.
[0078] (4) Synthesis of functionalized polymer: Take 2g of the polymer intermediate powder obtained in step (3) of this example and dissolve it in 50mL of dimethyl sulfoxide. Then add 2.4g of potassium carbonate and 1.2mL of iodomethane in sequence. React at room temperature in the dark for 24h. After the reaction is completed, slowly pour the polymer solution into 500mL of ethyl acetate to precipitate. After filtration, wash repeatedly with deionized water. Then place the purified product in an 80℃ vacuum drying oven and dry for 24h to obtain a light yellow functionalized polymer powder.
[0079] (5) Preparation of anion exchange membrane: Take 1g of the functionalized polymer powder obtained in step (4) of this embodiment and dissolve it in 8.2mL of dimethyl sulfoxide to obtain a film-forming solution with a target polymer mass concentration of 10%. Then, dry it at 100℃ by casting or casting method to obtain anion exchange membrane.
[0080] Example 3: m=0.2
[0081] (1) The synthesis of 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobine was the same as in Example 1, step (1);
[0082] (2) The synthesis of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine was the same as step (2) in Example 1;
[0083] (3) Synthesis of polymer intermediates: 1 g of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine and 2.7 g of m-terphenyl obtained in step (2) of this example were dissolved in 13.2 mL of dichloromethane. After complete dissolution, 2 g of N-methyl-4-piperidinone was added. Then, 10.6 mL of trifluoromethanesulfonic acid and 1.6 mL of trifluoroacetic acid were slowly added dropwise under ice bath to carry out Friedel-Crafts hydroxyalkylation reaction. After 4 h of reaction, a red viscous high molecular weight polymer was obtained. Then, a mixed solution of methanol and deionized water in a volume ratio of 1:1 was added to obtain a pure white fibrous polymer. After being cut into pieces, it was repeatedly washed with 1 M potassium carbonate aqueous solution and deionized water until the supernatant did not turn red after adding phenolphthalein indicator. Then, the purified product was placed in an 80 °C vacuum drying oven and dried for 24 h to obtain a light yellow polymer intermediate powder.
[0084] (4) Synthesis of functionalized polymer: Take 2g of the polymer intermediate powder obtained in step (3) of this example and dissolve it in 50mL of dimethyl sulfoxide. Then add 2.8g of potassium carbonate and 1.4mL of iodomethane in sequence. React at room temperature in the dark for 24h. After the reaction is completed, slowly pour the polymer solution into 500mL of ethyl acetate to precipitate. After filtration, wash repeatedly with deionized water. Then place the purified product in an 80℃ vacuum drying oven and dry for 24h to obtain a light yellow functionalized polymer powder.
[0085] (5) Preparation of anion exchange membrane: Take 1g of the functionalized polymer powder obtained in step (4) of this embodiment and dissolve it in 8.2mL of dimethyl sulfoxide to obtain a film-forming solution with a target polymer mass concentration of 10%. Then, dry it at 100℃ by casting or casting method to obtain anion exchange membrane.
[0086] Figure 1 The NMR 1H spectrum of the polymer intermediate (3) in Examples 1-3 is shown. The three curves from top to bottom correspond to the copolymer molar ratios m=0.05, m=0.1, and m=0.2, respectively. The spectrum shows all the characteristic absorption peaks of spirocyclic methyl, benzene ring hydrogen, and piperidine ring hydrogen in the chemical shift range of 1.0-10ppm. The peak positions correspond one-to-one with the target polymer skeleton, proving that the spirocyclic unit was successfully copolymerized and embedded in the molecular chain.
[0087] Figure 2The NMR spectra of the functionalized polymers (4) in Examples 1-3 are shown. The three curves from top to bottom correspond to the copolymer molar percentages m=0.05, m=0.1, and m=0.2, respectively. Figure 3 The presence of a characteristic proton peak for quaternary ammonium methyl groups near ppm, and the complete disappearance of the characteristic peak for piperidine cyclic tertiary amines, proves that piperidine is completely converted into quaternary ammonium cations.
[0088] The complete synthetic route of the spirobiinden and 9,9-dimethylfluorene copolymer quaternized polymer of the present invention is as follows, where m is the molar percentage of the spirobiinden unit copolymer, and the value ranges from 0.05 to 0.2.
[0089]
[0090] Example 4: m=0.05
[0091] (1) The synthesis of 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobine was the same as in Example 1, step (1);
[0092] (2) The synthesis of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine was the same as step (2) in Example 1;
[0093] (3) Synthesis of polymer intermediates: 1 g of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine and 11.2 g of 9,9-dimethylfluorene obtained in step (2) of this example were dissolved in 47 mL of dichloromethane. After complete dissolution, 7.5 g of N-methyl-4-piperidinone was added. Then, 36 mL of trifluoromethanesulfonic acid and 7.1 mL of trifluoroacetic acid were slowly added dropwise under ice bath to carry out Friedel-Crafts hydroxyalkylation reaction. After 5 h of reaction, a red viscous high molecular weight polymer was obtained. Then, a mixed solution of methanol and deionized water in a volume ratio of 1:1 was added to obtain a light yellow fibrous polymer. After being cut into pieces, it was repeatedly washed with 1 M potassium carbonate aqueous solution and deionized water until the supernatant did not turn red after adding phenolphthalein indicator. Then, the purified product was placed in an 80 °C vacuum drying oven and dried for 24 h to obtain a light yellow polymer intermediate powder.
[0094] (4) Synthesis of functionalized polymer: Take 2g of the polymer intermediate powder obtained in step (3) of this embodiment and dissolve it in 50mL of dimethyl sulfoxide. Then add 1g of potassium carbonate and 1mL of iodomethane in sequence. React at room temperature in the dark for 24h. After the reaction is completed, slowly pour the polymer solution into 500mL of ethyl acetate to precipitate. After filtration, wash repeatedly with deionized water. Then place the purified product in an 80℃ vacuum drying oven and dry for 24h to obtain a light yellow functionalized polymer powder.
[0095] (5) Preparation of ionomer solution: Take 1g of the functionalized polymer powder obtained in step (4) of this embodiment and dissolve it in 17mL of dimethyl sulfoxide to obtain a film-forming solution with a target polymer mass concentration of 5%. Then, after filtration and purification using a 0.45-micron polytetrafluoroethylene filter head, the ionomer of the high-performance anion exchange membrane polymer is obtained.
[0096] Example 5: m=0.1
[0097] (1) The synthesis of 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobine was the same as in Example 1, step (1);
[0098] (2) The synthesis of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine was the same as step (2) in Example 1;
[0099] (3) Synthesis of polymer intermediates: 1 g of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine and 5.2 g of 9,9-dimethylfluorene obtained in step (2) of this example were dissolved in 25 mL of dichloromethane. After complete dissolution, 4.8 g of N-methyl-4-piperidinone was added. Then, 24 mL of trifluoromethanesulfonic acid and 4 mL of trifluoroacetic acid were slowly added dropwise under ice bath to carry out Friedel-Crafts hydroxyalkylation reaction. After 4 h of reaction, a red viscous high molecular weight polymer was obtained. Then, a mixed solution of methanol and deionized water in a volume ratio of 1:1 was added to obtain a light yellow fibrous polymer. After being cut into pieces, it was repeatedly washed with 1 M potassium carbonate aqueous solution and deionized water until the supernatant did not turn red after adding phenolphthalein indicator. Then, the purified product was placed in an 80 °C vacuum drying oven and dried for 24 h to obtain a light yellow polymer intermediate powder.
[0100] (4) Synthesis of functionalized polymer: Take 2g of the polymer intermediate powder obtained in step (3) of this example and dissolve it in 50mL of dimethyl sulfoxide. Then add 1.2g of potassium carbonate and 1.5mL of iodomethane in sequence. React at room temperature in the dark for 24h. After the reaction is completed, slowly pour the polymer solution into 500mL of ethyl acetate to precipitate. After filtration, wash repeatedly with deionized water. Then place the purified product in an 80℃ vacuum drying oven and dry for 24h to obtain a light yellow functionalized polymer powder.
[0101] (5) Preparation of ionomer solution: Take 1g of the functionalized polymer powder obtained in step (4) of this embodiment and dissolve it in 17mL of dimethyl sulfoxide to obtain a film-forming solution with a target polymer mass concentration of 5%. Then, after filtration and purification using a 0.45-micron polytetrafluoroethylene filter head, the ionomer of the high-performance anion exchange membrane polymer is obtained.
[0102] Example 6: m=0.2
[0103] (1) The synthesis of 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobine was the same as in Example 1, step (1);
[0104] (2) The synthesis of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine was the same as step (2) in Example 1;
[0105] (3) Synthesis of polymer intermediates: 1 g of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobine and 2.3 g of 9,9-dimethylfluorene obtained in step (2) of this example were dissolved in 14 mL of dichloromethane. After complete dissolution, 2.3 g of N-methyl-4-piperidinone was added. Then, 16 mL of trifluoromethanesulfonic acid and 2.5 mL of trifluoroacetic acid were slowly added dropwise under ice bath to carry out Friedel-Crafts hydroxyalkylation reaction. After 2 h of reaction, a red viscous high molecular weight polymer was obtained. Then, a mixed solution of methanol and deionized water in a volume ratio of 1:1 was added to obtain a light yellow fibrous polymer. After being cut into pieces, it was repeatedly washed with 1 M potassium carbonate aqueous solution and deionized water until the supernatant did not turn red after adding phenolphthalein indicator. Then, the purified product was placed in an 80 °C vacuum drying oven and dried for 24 h to obtain a light yellow polymer intermediate powder.
[0106] (4) Synthesis of functionalized polymer: Take 2g of the polymer intermediate powder obtained in step (3) of this example and dissolve it in 50mL of dimethyl sulfoxide. Then add 1.5g of potassium carbonate and 2mL of iodomethane in sequence. React at room temperature in the dark for 24h. After the reaction is completed, slowly pour the polymer solution into 500mL of ethyl acetate to precipitate. After filtration, wash repeatedly with deionized water. Then place the purified product in an 80℃ vacuum drying oven and dry for 24h to obtain a light yellow functionalized polymer powder.
[0107] (5) Preparation of ionomer solution: Take 1g of the functionalized polymer powder obtained in step (4) of this embodiment and dissolve it in 17mL of dimethyl sulfoxide to obtain a film-forming solution with a target polymer mass concentration of 5%. Then, after filtration and purification using a 0.45-micron polytetrafluoroethylene filter head, the ionomer of the high-performance anion exchange membrane polymer is obtained.
[0108] Figure 3 The NMR 1H spectrum of the polymer intermediates of Examples 4-6 (3) is shown. The three curves from top to bottom correspond to the copolymer molar ratios m=0.05, m=0.1, and m=0.2, respectively. The characteristic hydrogen signals of spirocyclic, fluorene, and piperidine rings are fully present in the chemical shift range of 1.0-8ppm in the spectrum. The peak positions correspond one-to-one with the target polymer skeleton, verifying the structure of the copolymer product of spirocyclic and fluorene monomers.
[0109] Figure 4The figure shows the 1H NMR spectrum of the functionalized polymers of Examples 4-6 (4). The three curves from top to bottom correspond to the copolymer molar ratios m=0.05, m=0.1, and m=0.2, respectively. The characteristic peaks of spirocyclic, fluorene, and quaternary ammonium methyl groups are all matched, proving that the quaternization reaction is complete.
[0110] Comparative Example 1
[0111]
[0112] (1) Synthesis of polymer intermediates: 3g of m-terphenyl was dissolved in 15mL of dichloromethane. After complete dissolution, 2g of N-methyl-4-piperidinone was added. Then, 13mL of trifluoromethanesulfonic acid and 1.4mL of trifluoroacetic acid were slowly added dropwise under ice bath to carry out Friedel-Crafts hydroxyalkylation reaction. After 8h of reaction, a black viscous high molecular weight polymer was obtained. Then, a mixed solution of methanol and deionized water in a volume ratio of 1:1 was added to obtain a pure white fibrous polymer. After being cut into pieces, it was repeatedly washed with 1M potassium carbonate aqueous solution and deionized water until the supernatant did not turn red after adding phenolphthalein indicator. Then, the purified product was placed in an 80℃ vacuum drying oven and dried for 24h to obtain a light yellow polymer intermediate powder.
[0113] (2) Synthesis of functionalized polymer: Take 2g of polymer intermediate powder obtained in step (1) of this comparative example and dissolve it in 50mL of dimethyl sulfoxide. Then add 2.4g of potassium carbonate and 1.2mL of iodomethane in sequence. React at room temperature in the dark for 24h. After the reaction is completed, slowly pour the polymer solution into 500mL of ethyl acetate to precipitate. After filtration, wash repeatedly with deionized water. Then place the purified product in an 80℃ vacuum drying oven and dry for 24h to obtain a light yellow functionalized polymer powder.
[0114] (3) Preparation of anion exchange membrane: Take 1g of the functionalized polymer powder obtained in step (2) of this comparative example and dissolve it in 8.2mL of dimethyl sulfoxide to obtain a film-forming solution with a target polymer mass concentration of 10%. Then, dry it at 100℃ by casting or casting to obtain anion exchange membrane.
[0115] Figure 5 The 1H NMR spectrum of the polymer intermediate (1) of Comparative Example 1 shows that only the characteristic peaks of the meta-terphenyl and piperidine rings are present, and there are no characteristic signals of spirocyclic methyl and spirocyclic benzene rings, which directly proves that the comparative sample does not have a rigid spirocyclic structure.
[0116] Figure 6 The 1H NMR spectrum of the functionalized polymer (2) for comparison showed only signals of meta-terphenyl and quaternary ammonium methyl groups, with no spirocyclic characteristic peaks, and served as a performance reference sample.
[0117] Application Example 1
[0118] (1) Preparation of anion exchange membranes:
[0119] Weigh 1g of the pale yellow functionalized polymer powder prepared in Examples 1-3 and Comparative Example 1, and completely dissolve it in 20mL of dimethyl sulfoxide to prepare a homogeneous ionomer casting solution with a solid content of approximately 5wt%. Then, use a casting method to uniformly coat the casting solution onto a clean glass substrate surface, and place the glass substrate in a vacuum drying oven at 100℃ for 48 hours to thoroughly remove the solvent. After the system has naturally cooled to room temperature, remove it and immerse the substrate in deionized water for peeling and demolding. The resulting film is repeatedly washed and purified with deionized water, and the residual moisture on its surface is blotted dry with lint-free paper to obtain an anion exchange membrane with iodide ions as the counter ion.
[0120] (2) Construction of the catalyst layer:
[0121] The cathode catalyst, anode catalyst, and catalyst layer ionomer were mixed in a predetermined ratio and introduced into a mixed solvent of isopropanol and water to prepare a dispersion slurry with a solid content of 5 wt%. The slurry was then subjected to continuous ultrasonic vibration at -5°C for 2 hours until a highly dispersed, homogeneous fluid was obtained. Finally, the slurry was uniformly sprayed onto the surface of a porous substrate using a fully automated spraying device to form a catalyst layer.
[0122] (3) Counter ion exchange of anion exchange membranes:
[0123] The anion exchange membrane containing iodine counterions was completely immersed in a 1 mol / L potassium hydroxide aqueous solution and alkalized at room temperature for 48 hours, during which the alkali solution was replaced three times at fixed intervals to ensure complete ion exchange. After alkalization, the membrane was repeatedly rinsed with a large amount of deionized water until neutral, thus obtaining an anion exchange membrane in which the counterions were completely converted to OH⁻.
[0124] (4) Mechanical strength test:
[0125] The mechanical properties of the obtained membrane material were determined using an electronic universal testing machine at a constant tensile speed of 10 mm / min. The anion exchange membrane to be tested was finely cut into strips 60 mm long and 10 mm wide. The actual thickness of the samples was measured and recorded at multiple points using a micrometer. Three samples were tested in parallel for each group. Figure 7As shown, the curves include tensile stress-elongation curves for four sets of samples (comparative example, m=0.05, m=0.1, and m=0.2). Due to the introduction of the rigid monomer 6,6'-dimethoxy-3,3,3',3'-tetramethyl-1,1'-spirobiindenene, the polymer network receives strong rigid support, resulting in a significant improvement in its mechanical strength. Specifically, the tensile stress at break of the film with m=0.1 reaches 54.6 MPa, and the elongation at break is 15%; while the comparative polymer film without this rigid structure has a tensile stress at break and an elongation at break of only 38.3 MPa and 5.7%, respectively.
[0126] (5) Moisture content and swelling rate test:
[0127] The anion exchange membrane was cut into 4cm × 4cm square strips, placed in an 80℃ oven for complete dehydration and drying for 24 hours, and the dry membrane mass (W) was accurately weighed and recorded. dry ) and initial length of dry film (L) dry The sample was then immersed in a 1 mol / L KOH aqueous solution for complete alkalization and conversion, followed by washing with deionized water until neutral to obtain an OH⁻ type membrane. The membrane was then transferred to deionized water and immersed at different temperature gradients from 30℃ to 80℃. Every 12 hours, the sample was removed, the surface free water was quickly wiped dry, and the wet membrane mass (W) was immediately measured. wet ) and wet film length (L) wet The water content and swelling ratio of the membrane are calculated according to the following formula:
[0128] ;
[0129] ;
[0130] In the formula, WU represents the moisture content, and SR represents the swelling rate;
[0131] Based on the measurement results at different temperatures, a response curve of moisture content as a function of temperature was plotted, such as... Figure 8 As shown, across the entire temperature range of 20–80℃, the water content of the spirocyclic sample was consistently higher than that of the comparative sample. At 80℃, the water absorption rate of the film with m=0.1 reached 103.7%, while the comparative sample's water absorption rate was 64%. This indicates that the spirocyclic rings widen the intermolecular gaps, increasing the free volume within the film. This large free volume structure significantly enhances its ability to capture and lock in water molecules. The response curve of swelling ratio as a function of temperature is plotted, as shown below. Figure 9As shown, although the spirocyclic sample absorbs more water, in a high-temperature water environment of 80℃, the linear swelling rate of the m=0.1 film is only 29%, while the swelling rate of the comparative sample is 20.2%, with a very small difference between the two. This proves that although the m=0.1 film has a higher water content, thanks to the strong spatial confinement effect of the rigid backbone on chain segment creep, and the constraint of molecular chain extension by the three-dimensional rigid structure of the spirocyclic ring, it still maintains an excellent dimensional anti-swelling structure at high temperatures, breaking through the industry trade-off bottleneck.
[0132] (6) Hydroxide ion conductivity test of anion exchange membrane
[0133] The ion conductivity of the membrane was determined using the four-electrode AC impedance method. Anion exchange membranes were cut into strips of 1cm × 4cm, fixed in a specially designed test fixture, and completely immersed in an electrolytic cell filled with pure water. An electrochemical workstation was connected, and impedance spectroscopy was performed under a constant AC current excitation mode of 0.1mA, with the scanning frequency range set from 1MHz to 100MHz. A plateau region with stable impedance values was selected from the obtained Bode plot, and the corresponding actual membrane resistance R was read. The hydroxide ion conductivity of the membrane was calculated using the following formula:
[0134] ;
[0135] In the formula, σ represents the hydroxide ion conductivity, L represents the length of the anion exchange membrane, and R represents the cross-sectional area of the anion exchange membrane.
[0136] Based on the resistance values measured at different temperatures, a kinetic curve of the hydroxide ion conductivity versus temperature was plotted, as shown below. Figure 10 As shown. By Figure 10 It can be seen that the conductivity of all spirocyclic modified samples in the 20~80℃ range is significantly higher than that of the comparative sample. Under the high temperature condition of 80℃, the hydroxide ion conductivity of the m=0.1 anion exchange membrane is as high as 180mS / cm, while the conductivity of the comparative sample under the same conditions is only 103mS / cm. This fully demonstrates that the high free volume rigid continuous channel constructed by the present invention has a significant promoting effect on chemical ion conduction, which can reduce the ohmic internal resistance of the electrolyzer and reduce power consumption.
[0137] (7) Testing of polarization performance of full cells in water electrolyzers with different membrane materials
[0138] The films prepared in Examples 1-3 and Comparative Example 1 were assembled into single cells for polarization curve determination. The effective reaction area of the single cell was 1.0 cm². 2The cathode and anode used Pt / Ni and NiFe-LDH catalysts, respectively, with the catalyst loading on the membrane surface strictly controlled to be consistent. Tests were conducted at a constant operating temperature of 60℃, with a 1 mol / L KOH aqueous solution continuously circulated into the anode of the electrolyzer. Using an electrochemical workstation and the steady-state voltage step method, the cell current density response of the single cell at different voltages was recorded. The resulting single-cell polarization curves are shown below. Figure 11 As shown. By Figure 11 The polarization test results show that, at an operating temperature of 60℃, the electrolyzer equipped with an m=0.1 anion exchange membrane exhibits a significantly reduced electrolysis overpotential. At a standard cell voltage of 2.0V, the single cell based on the m=0.1 anion exchange membrane achieves a current density as high as 4.6 A / cm². 2 In contrast, the single cell using a comparative film exhibits a current density of only 3.0 A / cm² at the same 2.0 V tank voltage. 2 The dramatic improvement in the polarization performance of this full cell is due, on the one hand, to the ultra-high hydroxide conductivity brought about by the rigid porous structure, which significantly reduces the ohmic internal resistance of the cell; on the other hand, the excellent anti-swelling dimensional stability of the membrane under high-temperature alkaline solutions ensures close contact between the membrane and the catalyst layer at the three-phase interface, effectively suppressing the surge in mass transfer impedance caused by interfacial peeling under high current densities. This indicates that the anion exchange membrane prepared in this invention has excellent application potential in industrial-scale high-current-density hydrogen production.
[0139] (8) Electrolytic cell polarization performance test of different ionomer binders
[0140] This test maintains the core membrane configuration of m=0.1 and evaluates the full-cell polarization performance of the polymer material used as an ionomer by varying the composition of the ionomer binder within the catalyst layer on the electrode surface. Examples 4-6 were used as the catalyst layer ionomer binder. The mass percentage of the ionomer in the catalyst layer was uniformly set to 15 wt%. The tests were conducted at 60°C under 1 mol / L KOH circulating alkaline conditions, and the single-cell polarization curves based on different ionomer formulations are shown below. Figure 12 As shown. Figure 12 The polarization curves show that the single cell using Example 2 as the catalyst ionomer exhibits superior full-cell polarization performance compared to the other example groups. At 60°C and a cell voltage of 2V, the current density of the Example 2 ionomer group reaches 6.5A / cm². 2This results in extremely high voltage efficiency and catalyst utilization. This is due to the introduction of a non-planar rigid spirocyclic double indene structure, which endows the ionomer with greater skeletal flexibility and a larger free volume at the microscopic level. At the three-phase interface, it not only provides denser hydrophilic quaternary ammonium cation sites but also forms regular localized porous mass transfer channels on the catalyst particle surface, significantly accelerating the gas escape of water and oxygen products and the local mass transfer of reactants. These results demonstrate its outstanding value as a high-performance catalyst layer ionomer binder in the construction of electrolyzer electrodes.
[0141] The spirocyclic quaternized polymer prepared by this invention can be directly used as a solid membrane in anion exchange membrane water electrolyzer, or as a binder for ionomers in electrode catalyst layers. The main chain of the material has no easily hydrolyzable aromatic ether bonds, and the steric hindrance of the spirocyclic rings prevents nucleophilic attack by hydroxide ions, exhibiting excellent long-term stability in strong bases. It has broad application prospects in electrochemical energy conversion fields such as alkaline water electrolysis for hydrogen production and anion exchange membrane fuel cells.
[0142] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the invention. Various variations can be made to the above embodiments of the present invention. That is, all simple and equivalent changes and modifications made based on the claims and description of this invention fall within the protection scope of the claims. All aspects not described in detail in this invention are conventional technical content.
Claims
1. An anion exchange membrane containing a spirocyclic structure, characterized in that, The quaternized copolymer polymer constituting this anion exchange membrane has an all-carbon backbone without aromatic ether bonds, and its structural formula is as follows: In the formula: Ar is an aryl monomer, R is any one or more of C1~C10 alkyl or haloalkyl, and x = 0.05~0.
2.
2. The anion exchange membrane containing a spirocyclic structure according to claim 1, characterized in that, The aryl monomer includes any one or more of the following structures: 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 。 3. The anion exchange membrane containing a spirocyclic structure according to claim 1, characterized in that, The polymer's all-carbon backbone simultaneously incorporates orthogonally twisted 6,6'-dialkoxy-3,3,3',3'-tetramethyl-1,1'-spirobiinden rigid units and aryl copolymer units, with piperidine quaternary ammonium groups directly bonded to the polymer backbone.
4. The anion exchange membrane containing a spirocyclic structure according to claim 3, characterized in that, The aryl copolymer unit is selected from one of m-terphenyl and 9,9-dimethylfluorene.
5. A method for preparing the anion exchange membrane according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1, the aryl structure reactant and the ketone reactant are dissolved in the first organic solvent and reacted under superacid catalysis to obtain a polymer solution with piperidine structure. Then, the solution is added to the first precipitant for precipitation, washing and drying to obtain a polymer powder with piperidine structure. S2, dissolve the polymer powder with piperidine structure in a second organic solvent, react with a methylating agent and a basic agent, then add a second precipitant to precipitate, wash and dry to obtain quaternized polymer powder; S3, dissolve the quaternized polymer powder in a third organic solvent, and then dry the solvent to obtain an ion exchange membrane.
6. The preparation method according to claim 5, characterized in that, The ketone reactants include one or more of the following carbonyl compound structures: 、 、 、 、 、 、 、 。 7. The preparation method according to claim 5, characterized in that, In step S1, the molar ratio of aryl structure reactant to ketone reactant is 1:(1.1~1.2), and the molar ratio of aryl structure reactant, first organic solvent, and superacid is 1:(50~120):(10~40).
8. The preparation method according to claim 5, characterized in that, In step S2, the molar ratio of the second organic solvent, the methylating agent, and the basic agent is (100~200):(2~10):(1~5).
9. An electrochemical device, characterized in that, An anion exchange membrane obtained by molding the quaternized copolymer polymer according to any one of claims 1 to 4.
10. The electrochemical device according to claim 9, characterized in that, The quaternized copolymer polymer can be formed into a self-standing film for use as a solid membrane in anion exchange membrane water electrolyzer, and / or dispersed in the catalyst layer as an electrode catalyst layer ionomer binder.